Learning history in an open system: Creating histories for sustainable futures. Issue 1 (February 2015) - Gearty, Margaret R; Bradbury-Huang, Hilary; Reason, Peter
What kind of learning is required to bring us towards a more sustainable future? We argue that when behaviourally and technically complex issues intertwine, a collaborative social learning process that engages diverse actors in deep systems change is necessary. The learning required includes but overtakes debate, bringing organisations, individuals and communities into cycles of experiential, cumulative, ad hoc and opportunistic, yet systematic, learning. Current conceptualisations and approaches to learning have not been framed with the requisite level of integrated complexity given our sustainability challenges. This article introduces the action research approach of 'learning history in an open system' in the service of such learning. Updating the heretofore single-project focussed learning history, we present recent methodological developments for its use in open systems that support a joining up of projects and sites of endeavour to support deeper and accumulating systems' learning. We explore the links to learning literature drawing on developments in aesthetics and arts-based action research to suggest our approach is one useful way of responding to the more general challenge of scale that concerns action researchers.